Tanggung Jawab Notaris Atas Keterangan Palsu Dalam Akta Rapat Umum Pemegang Saham Luar Biasa - Anisa Nabila Hamdi; Mohammad Fajri Mekka Putra (UNES Law Review, 2024)
The authority of a notary is to make authentic deeds regarding all acts, agreements, and stipulations required by statutory regulations and/or desired by those interested to be stated in an authentic deed. A notary is obliged to guarantee the truth of the deeds they make; therefore, a notary must act honestly, fairly, and transparently in making an authentic deed. However, notaries often act carelessly and are not thorough in carrying out their duties and positions, which can lead to legal problems in both the legal and criminal realms. The issues discussed below concern the responsibilities of a notary who includes false information in making a deed for an extraordinary general meeting of shareholders and the legal consequences of a notarial deed that includes false information. The type of research used to address this problem is normative legal research, descriptive in nature. The data used is secondary data analyzed qualitatively, and the method of drawing conclusions uses deductive logic. Based on the research results, a notarial deed containing elements of a criminal act can render the notary criminally liable under Article 55 and Article 56 of the Criminal Code due to negligence in falsifying documents. This can result in the notarial deed being annulled or nullified by law..